PPARα-Independent Arterial Smooth Muscle Relaxant Effects of PPARα Agonists. (11th September 2012) - Silswal, Neerupma; Parelkar, Nikhil K.; Wacker, Michael J.; Badr, Mostafa; Andresen, Jon
Abstract : We sought to determine direct vascular effects of peroxisome proliferator-activated receptor alpha (PPAR α ) agonists using isolated mouse aortas and middle cerebral arteries (MCAs). The PPAR α agonists GW7647, WY14643, and gemfibrozil acutely relaxed aortas held under isometric tension and dilated pressurized MCAs with the following order of potency: GW7647≫WY14643>gemfibrozil. Responses were endothelium-independent, and the use of PPAR α deficient mice demonstrated that responses were also PPAR α -independent. Pretreating arteries with high extracellular K + attenuated PPAR α agonist-mediated relaxations in the aorta, but not in the MCA. In the aorta, the ATP sensitive potassium (K ATP ) channel blocker glibenclamide also impaired relaxations whereas the other K + channel inhibitors, 4-aminopyridine and Iberiotoxin, had no effect. In aortas, GW7647 and WY14643 elevated cGMP levels by stimulating soluble guanylyl cyclase (sGC), and inhibition of sGC with ODQ blunted relaxations to PPAR α agonists. In the MCA, dilations were inhibited by the protein kinase C (PKC) activator, phorbol 12, 13-dibutyrate, and also by ODQ. Our results demonstrated acute, nonreceptor-mediated relaxant effects of PPAR α agonists on smooth muscle of mouse arteries. Responses to PPAR α agonists in the aorta involved K ATP channels and sGC, whereas in the MCA the PKC and sGC pathways also appeared to contribute to the response.